Preoperative Clostridium difficile Infection Does Not Affect Pouch Outcomes in Patients with Ulcerative Colitis Who Undergo Ileal Pouch-anal Anastomosis. Issue 7 (13th April 2017) - Lightner, Amy L.; Tse, Chung Sang; Quinn, Kevin; Bergquist, John R.; Enders, Felicity; Pendegraft, Richard; Khanna, Sahil; Raffals, Laura
Abstract : Background: The operation of choice for patients with chronic ulcerative colitis (CUC) is restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA). Pouchitis is the most common complication after IPAA. The incidence of Clostridium difficile infection (CDI) is higher in CUC patients than the general population and can lead to significant disease flares and higher rates of colectomy. We sought to determine the risk of pouchitis in patients with precolectomy CDI and 90-day postoperative IPAA complications. Methods: A retrospective case–control study was conducted on patients with CUC who underwent an IPAA between January 1, 2000 and January 10, 2015. The study cohort was comprised of patients diagnosed with CDI within 90 days before colectomy; patients with CUC without CDI comprised the control cohort. The primary outcome measure was the frequency of pouchitis after IPAA. Secondary outcomes included time to pouchitis, 90-day postoperative pouch morbidity: surgical site infection, hemorrhage, anastomotic leak, fistula formation, pouchitis treatment and response, and pouch failure requiring end-ileostomy or fecal diversion. Univariate and multivariable analysis was used to determine differences between CDI and non-CDI groups. Results: Forty-eight case patients and 154 control patients were included. Patients with preoperative CDI were younger ( P = 0.010), had higher rates of medically refractory disease ( P = 0.002), and had greater use of biologic therapy ( P = 0.046). The rate of pouchitis was 50.0% (n = 24) and 46.8% (n = 72) ( P = 0.694) among patients with and without preoperative CDI, respectively. Patients with preoperative CDI who developed pouchitis post-IPAA were more likely to require medical management with an anti-TNFα ( P = 0.042) and surgical management with end/diverting ileostomy ( P = 0.042). Preoperative CDI was associated with higher rates of postoperative IPAA anastamotic or pouch strictures ( P = 0.018). Multivariable analysis revealed primary sclerosing cholangitis (PSC) as the only variable associated with increased risk for pouchitis (OR 10.59; 95% CI, 3.07–51.08; P < 0.001). Conclusions: Preoperative CDI does not seem to be associated with an increased risk of pouchitis in patients with CUC.